Employer's implied obligation in construction contract - Tazol Arrief, Nurulain (2013)
The employer’s implied obligation is one of significant elements in the construction contract as there is a few of express obligations for employer in the standard form of contract. A breach of implied obligation carries the same weight as the breach for express obligation. However, this implied obligation has a certain extent to which it is imply as there are conditions to be fulfilled before a term is implied into a contract. For employer, there are two types of implied obligation, duty to cooperate which also known as positive implied obligation and another one is the duty not to interfere or prevent which also known as negative implied obligation. These positive and negative implied obligations give rise to a duty to co-operate from the employer in every works to make the contract workable. Due to the nature of construction contract that involved a lot of works, there are certain works that demand the cooperation from the employer such as giving possession and access to the site, supply information and appoint competence contract administrator. This implication will need to follow certain principle before it can be imposed as the extent of employer’s implied obligation. Therefore this research is carried out to identify the extent of the employer’s implied obligation in the construction contract. This is basically a descriptive research and the methodology used is essentially based on case law analysis and review. The cases are retrieved from the Lexis Malaysia online database. All the cases are in the scope of construction contract. The analysis revealed that, the employer’s implied obligation will have certain extent and the employer’s implied obligation will have certain requirement to be implied.